2023
DOI: 10.1021/acsnano.2c06233
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase-Sensitive T1 and T2 Switchable MR Imaging for Diagnosis of Nonalcoholic Steatohepatitis

Abstract: Nonalcoholic steatohepatitis (NASH) is the critical stage in the development of nonalcoholic fatty liver disease (NAFLD) from simple and reversible steatosis to irreversible cirrhosis and even hepatocellular carcinoma (HCC). Thus, the diagnosis of NASH is important for preventing the progress of NAFLD into a fatal condition. The oxidative enzyme myeloperoxidase (MPO), which is mostly produced by polymorphonuclear neutrophil granulocytes (NEU), has been identified as a key player in lipid peroxidation in inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…In addition, Yang et al recently reported that a self-expanding, endoscopically deliverable, and viscous hydrogel can be used to prevent gastric perforation. 95 They found that the silicon dioxide coating significantly increased the adhesive strength of the hydrogel in a simulated highly acidic stomach environment. Acid-resistant, tough, and elastic double-network hydrogels were designed using dimethylacrylamide (DMA) and biodegradable cross-linking agents ( N , N ′-cysteamine bis (acrylamide) (CBA) and sodium alginate (SA)) used to crosslink calcium ions.…”
Section: Application Of Different Adhesive Materials In the Biomedica...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Yang et al recently reported that a self-expanding, endoscopically deliverable, and viscous hydrogel can be used to prevent gastric perforation. 95 They found that the silicon dioxide coating significantly increased the adhesive strength of the hydrogel in a simulated highly acidic stomach environment. Acid-resistant, tough, and elastic double-network hydrogels were designed using dimethylacrylamide (DMA) and biodegradable cross-linking agents ( N , N ′-cysteamine bis (acrylamide) (CBA) and sodium alginate (SA)) used to crosslink calcium ions.…”
Section: Application Of Different Adhesive Materials In the Biomedica...mentioning
confidence: 99%
“…32,94 Therefore, after modifying some of their functional sites using chemical or bioengineering methods, an increasing number of composite adhesive materials have been prepared, including composites formed between viscous biomolecules, composites between biomolecules, and chemical modification. 95 There are many methods used to prepare composite adhesive materials, which can be roughly divided into physical mixing, modular gene, and chemical grafting methods. 22…”
Section: Compound Adhesive Materialsmentioning
confidence: 99%
“…Among a wide variety of CAs, iron oxide nanoparticles (IONPs) have been developed as promising MRI CAs, which can provide high-sensitivity contrast due to their potent superparamagnetic properties . Recently, several sensitive and targeted IONPs have been developed for MR detection and grading of liver diseases using a 7 or 9.4 T MR system. , However, the increase of magnetic field strength significantly improves the resolution but also elevates the cost and price, reducing the clinical feasibility. Therefore, novel CAs should be developed to overcome the shortcomings of low tissue resolution caused by low magnetic field strength on the clinical 3 T MR system.…”
Section: Introductionmentioning
confidence: 99%
“…It can react with the aldehyde group on allylsine, the product of LOX, to turn on its fluorescence. Subsequently, we applied TPAH to monitor fibrosis along with NASH progression using methionine- and choline-deficient (MCD) diet-fed mice as the model. - Early-stage fibrosis was observed in MCD diet-fed mice from 8 weeks onward. Notably, the administration of an LOX inhibitor for two weeks significantly reduced the fibrosis, as evident by Picrosirius Red staining and in vivo fluorescence signal after TPAH injection, suggesting the role of LOX activity in fibrosis progression.…”
Section: Introductionmentioning
confidence: 99%